Caesarean section audit spiral spanning 6 years of management in 3 major obstetric units of Glasgow. (18th April 2012) - Naz, A; Gibson, J; Hardwick, C; Moss, H
Abstract : Background: Caesarean section(CS) rates in Scotland have increased from 8.6% in 1976 to 25.4% in 2010.1 Aims & Objectives: In this study, we appraised the management of caesarean section against NICE and local guidelines, 2 with a view to target any areas of improvement. Specific objectives included a review of operative technique, type of anaesthetic and fetal distress parameters. Materials & Methods: Retrospective data collection of caesarean sections during a 2 week period. The audits were carried out in June 2005, November 2006 and January 2011. Results: All women received thromboprophylaxis. 95 % of CS were performed under regional anaesthetic. Umbilical cord pH performed in 75% of emergency CS. Decision to delivery times for the most urgent CS have reduced from a median of 33 (range 20-60) to 26 minutes (range 20-36 minutes)